Conversion of Plastic Waste into Supports for Nanostructured Heterogeneous Catalysts: Application in Environmental Remediation - Geovânia Cordeiro de Assis; Roberta Anjos de Jesus; Wélida Tamires Alves da Silva; Luiz Fernando Romanholo Ferreira; Renan Tavares Figueiredo; Rodrigo José de Oliveira (Surfaces, 2021)
Plastics are ubiquitous in our society and are used in many industries, such as packaging, electronics, the automotive industry, and medical and health sectors, and plastic waste is among the types of waste of higher environmental concern. The increase in the amount of plastic waste produced daily has increased environmental problems, such as pollution by micro-plastics, contamination of the food chain, biodiversity degradation and economic losses. The selective and efficient conversion of plastic waste for applications in environmental remediation, such as by obtaining composites, is a strategy of the scientific community for the recovery of plastic waste. The development of polymeric supports for efficient, sustainable, and low-cost heterogeneous catalysts for the treatment of organic/inorganic contaminants is highly desirable yet still a great challenge; this will be the main focus of this work. Common commercial polymers, like polystyrene, polypropylene, polyethylene therephthalate, polyethylene and polyvinyl chloride, are addressed herein, as are their main physicochemical properties, such as molecular mass, degree of crystallinity and others. Additionally, we discuss the environmental and health risks of plastic debris and the main recycling technologies as well as their issues and environmental impact. The use of nanomaterials raises concerns about toxicity and reinforces the need to apply supports; this means that the recycling of plastics in this way may tackle two issues. Finally, we dissert about the advances in turning plastic waste into support for nanocatalysts for environmental remediation, mainly metal and metal oxide nanoparticles.